Maritime power and China's grand strategy - Chawla, Anil Kumar (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2025)
"This book examines the role of maritime power in the 'Chinese Dream' of becoming the pre-eminent global power by 2049, a century after the establishment of the People's Republic of China (PRC). The book argues that China seeks to use its maritime power as part of its quest to attain Great Power status by employing it to these areas: provide deterrence in the maritime domain; assure availability of resources; protecting its sea lines of communication; and in the economic domination of specific developing countries in Asia, Africa, Oceania and South America. Based on a careful examination of primary sources, especially China's defence white papers and essential works on the topic by prominent Chinese military analysts and institutions, the author systematically unpacks interpretations and analysis of China's evolving concepts of maritime power. The book traces China's development and use of maritime power over its long-recorded history, especially from the time it became the People's Republic of China (1950) to the present (2024) and links the country's maritime past with the present. A comprehensive and detailed study of the evolution of Chinese concepts of maritime power and how it forms an important part of the rejuvenation of the nation and the projection of China as a global power by mid-century, this book will be of interest to researchers studying Asian and Chinese Studies, Military Studies and policy makers at think tanks and government agencies"--
The Historical Context of China's Maritime Power -- The Evolution of China's Military Strategy -- The Evolution of China's Maritime Strategy -- China's Maritime Strategy in the South China Sea -- A Case Study -- Strategy for Build-up of China's Comprehensive Maritime Power -- Maritime Dimension of the Belt and Road Initiative.
Keywords: Sea-power -- China -- History; Naval strategy; China -- Military policy; POLITICAL SCIENCE / International Relations / General